'Visualizing dysfluency': An interview with Conor Foran. Issue 2 (1st December 2020) - Foran, Conor; Stuart, Maria; Martin, Daniel
In 2018, designer Conor Foran presented his work on Dysfluent Mono, a typeface that represents the vocal repetitions of stammered speech, at the symposium Metaphoric Stammers and Embodied Speakers at University College Dublin, Ireland. In 2020, Foran self-published the first issue of Dysfluent Magazine, a magazine about the positive experiences of people who stutter that is set exclusively in Dysfluent Mono. Maria Stuart and Daniel Martin had the occasion to interview Foran on his work in both typography and advocacy for people who stutter.